Structure and Biocatalytic Scope of Coclaurine N‐Methyltransferase - Bennett, Matthew R. (Angew Chem Int Ed Engl, 2018)
Benzylisoquinoline alkaloids (BIAs) are a structurally diverse family of plant secondary metabolites, which have been exploited to develop analgesics, antibiotics, antitumor agents, and other therapeutic agents. Biosynthesis of BIAs proceeds via a common pathway from tyrosine to (S)‐reticulene at which point the pathway diverges. Coclaurine N‐methyltransferase (CNMT) is a key enzyme in the pathway to (S)‐reticulene, installing the N‐methyl substituent that is essential for the bioactivity of many BIAs. In this paper, we describe the first crystal structure of CNMT which, along with mutagenesis studies, defines the enzymes active site architecture. The specificity of CNMT was also explored with a range of natural and synthetic substrates as well as co‐factor analogues. Knowledge from this study could be used to generate improved CNMT variants required to produce BIAs or synthetic derivatives.